ANALISIS AKUNTABILITAS DAN TRANSPARANSI PELAPORAN KEUANGAN DALAM MENINGKATKAN PENERIMAAN DANA PADA BAZNAS - Ulinnuha, Tri Rizqi; Nabila, Fitri; Novitasari, Rinjani; Mulyani, Ade Sri (Universitas Trilogi, 2024)
This study aims to analyze the accountability and transparency of financial reporting in increasing the receipt of funds at Baznas. The research method used is a literature study with a qualitative approach by collecting information from relevant written sources aimed at obtaining in-depth insights and strong theories to support this research and the type of secondary data obtained from www.baznas.go.id in the form of financial reports and zakat reports. The results of the analysis that has been done, it can be seen that in its accountability BAZNAS has presented accountable financial statements in accordance with the accounting standards set out in PSAK 109. In managing its funds, BAZNAS has received funds of 58% in 2022 with the majority of funds obtained from Zakat Maal and distributed funds of 54%, thus the funds distributed are proportional to the funds obtained, this states that BAZNAS has been responsible for the funds received from donors. BAZNAS also presents its financial statements on its official website that can be accessed by the public as a form of transparency.Keywords: Accountability; Baznas; Non-Profit Organizations; Transparency; ZIS Funds